Bridging digital capabilities and financial resilience: A comparative study of FinTech, AI literacy, and financial inclusion among households in Malaysia and Indonesia - Sabri, Mohamad Fazli; Trinugroho, Irwan; Magli, Amirah Shazana; Law, Siong Hook; Wahyono, Budi; Ridhwan, Masagus M.; Septianto, Fadli (Elsevier B.V., 2026)
Digital financial services increasingly operate within AI-mediated commerce ecosystems, yet meaningful participation depends not only on access but on users’ ability to convert digital capabilities into sustained financial behaviour. This study proposes and empirically validates the Behavioural–Capability Model of FinTech Empowerment (BCMFE), an integrative framework that synthesises the Capability Approach, the Cognitive–Behavioural View (CBV), and UTAUT2 to explain how AI literacy, financial literacy, digital financial literacy, FinTech adoption, and financial resilience jointly shape digital financial inclusion (DFI). Using survey data from 1150 respondents in Malaysia and Indonesia and applying Partial Least Squares Structural Equation Modelling with multi-group analysis, the findings reveal three novel insights. First, digital financial literacy and FinTech adoption emerge as dominant capability drivers of inclusion. Second, financial resilience functions as a critical behavioural conversion mechanism linking cognitive and digital capabilities to sustained platform engagement. Third, AI literacy exhibits asymmetric effects across institutional contexts—neutral in Malaysia but negatively associated with inclusion in Indonesia—highlighting the moderating role of regulatory maturity and digital governance. By reframing DFI as a capability-conversion process rather than a linear adoption outcome, the BCMFE advances electronic commerce research and offers a human-centred framework for AI-enabled financial ecosystems in emerging economies.